Hot π‐Electron Tunneling of Metal–Insulator–COF Nanostructures for Efficient Hydrogen Production. Issue 50 (12th November 2019) - Ming, Jintao; Liu, Ai; Zhao, Jiwu; Zhang, Pu; Huang, Haowei; Lin, Huan; Xu, Ziting; Zhang, Xuming; Wang, Xuxu; Hofkens, Johan; Roeffaers, Maarten B. J.; Long, Jinlin
Abstract: A metal–insulator–semiconductor (MIS) photosystem based on covalent organic framework (COF) semiconductors was designed for robust and efficient hydrogen evolution under visible‐light irradiation. A maximal H2 evolution rate of 8.42 mmol h −1  g −1 and a turnover frequency of 789.5 h −1 were achieved by using a MIS photosystem prepared by electrostatic self‐assembly of polyvinylpyrrolidone (PVP) insulator‐capped Pt nanoparticles (NPs) with the hydrophilic imine‐linked TP‐COFs having =C=O−H−N= hydrogen‐bonding groups. The hot π‐electrons in the photoexcited n‐type TP‐COF semiconductors can be efficiently extracted and tunneled to Pt NPs across an ultrathin PVP insulating layer to reduce protons to H2 . Compared to the Schottky‐type counterparts, the COF‐based MIS photosystems give a 32‐fold‐enhanced carrier efficiency, attributed to the combined enhancement of photoexcitation rate, charge separation, and oxidation rate of holes accumulated in the valence band of the TP‐COF semiconductor. Abstract : COFing hydrogen : A MIS (metal–insulator–semiconductor) photosystem can efficiently extract hot π‐electrons of n‐type organic COF semiconductors for hydrogen production and gain a 32‐fold‐enhanced carrier efficiency and an impressive turnover frequency of 789.5 h −1 under visible light excitation.